Diabetes and thrombolysis for acute stroke: a clear benefit for diabetics. (21st September 2013) - Reiter, M.; Teuschl, Y.; Matz, K.; Seyfang, L.; Brainin, M.; ,
<x xml:space="preserve">Abstract</x> Background and purpose Diabetes is a predictor for poor outcome after thrombolysis in stroke patients, and early post‐stroke glycaemia is associated with higher rates of post‐thrombolytic symptomatic intracerebral haemorrhages (SICHs). Diabetic stroke patients may nevertheless profit from thrombolysis. Here, we compared outcome data of matched thrombolysed and non‐thrombolysed diabetic and non‐diabetic stroke patients from a national database. Methods The outcomes of 1079 matched quadruples, each consisting of a thrombolysed diabetic, a non‐thrombolysed diabetic, a thrombolysed non‐diabetic and a non‐thrombolysed non‐diabetic case (a total of 4316 cases), enrolled in the Austrian Stroke Unit Registry (2004–2013), were compared. Patients were matched according to sex, age, stroke severity, pre‐stroke disability and prior stroke. Results A regression model with improvement as depending variable found no effect of diabetes (P = 0.158) or the interaction diabetes × thrombolysis (P = 0.507), whereas the effect of thrombolysis itself was highly significant (P < 0.001). Functional outcome (modified Rankin Scale) was significantly better in thrombolysed than in non‐thrombolysed diabetic patients at discharge from the stroke‐unit (P < 0.001) and 3 months later (P = 0.006). No significant differences were found in the number of SICHs after thrombolytic treatment between diabetic (4.9%) and non‐diabetic strokes (3.5%). Both groups had a higher risk of SICH compared with the non‐thrombolysed groups (diabetics 2.6%, non‐diabetics 2.5%). Due to lack of documentation, the effect of admission blood glucose on SICH was not investigated. Conclusions Data from this nationwide survey show that diabetic stroke patients receive a substantial benefit from thrombolysis, and therefore diabetic strokes should not be excluded from thrombolytic treatment.